2022
DOI: 10.3389/fendo.2022.917838
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Composite Indicator of Predicting Mortality Risk for Heart Failure Patients With Diabetes Admitted to Intensive Care Unit Based on Machine Learning

Abstract: BackgroundPatients with heart failure (HF) with diabetes may face a poorer prognosis and higher mortality than patients with either disease alone, especially for those in intensive care unit. So far, there is no precise mortality risk prediction indicator for this kind of patient.MethodTwo high-quality critically ill databases, the Medical Information Mart for Intensive Care IV (MIMIC-IV) database and the Telehealth Intensive Care Unit (eICU) Collaborative Research Database (eICU-CRD) Collaborative Research Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Although our identified models have a ‘fair’ predictive capacity (close to ‘good’), their estimated AUC is generally lower than the previous studies 9 , 12 , 14 , 15 . This state of affairs can be attributed in part to the availability of clinical information regarding the laboratory tests and vital signs that were used in the previous investigations, whereas in our study none of these information were used.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Although our identified models have a ‘fair’ predictive capacity (close to ‘good’), their estimated AUC is generally lower than the previous studies 9 , 12 , 14 , 15 . This state of affairs can be attributed in part to the availability of clinical information regarding the laboratory tests and vital signs that were used in the previous investigations, whereas in our study none of these information were used.…”
Section: Discussionmentioning
confidence: 51%
“…In another study 14 , the mortality of heart failure patients with diabetes was predicted using nine classifiers, including LR, RF, SVM, KNN, DT, GBM, XGBoost, LightGBM, and Bagging. The RF algorithm outperformed other algorithms, achieving an AUC of 0.92.…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of machine learning methods have been successfully applied to medicine with great flexibility and precision and have been employed in early diagnosis, risk stratification, and trend prediction. It has previously been reported that machine learning models have been used in cardiology for predicting survival in patients with HF and its complications (39)(40)(41). In this study, machine learning techniques were applied to develop the first prediction model that could be used to predict the mortality risk in HF patients with HH accurately.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, a new model is created to reduce the errors of the previous model [27]. LR was chosen for its simplicity and interpretability in terms of a broad application, XGBoost for its accuracy, performance, and handling of complex, high-dimensional, and imbalanced data [28][29][30].…”
Section: Model Developmentmentioning
confidence: 99%